KAJIAN TENTANG PERANCANGAN ALAT DAN SISTEM AUTO FOKUS CITRA DENGAN METODE CONTRAST MEASURE - Suwandy Suwandy (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Tools and application programs that created is a tool that is integrated with the microscope to capture images of blood cells automatically and calculate the focus of the image automatically with Contrast Measure method and an application to detect and do a recognition in the white blood cells. Images taken from a single slide preparation can be the image of red blood cells and white blood cells. To distinguish red blood cells and white blood cells detection is carried out based on pixel image . The recognition is done by calculating characteristic values with the co-occurrence matrix. Based on the results of testing auto focus system is able to run properly to determine whether focus or not the image with successfull percentage  at 100%. While the recognition of the red blood cells are less goes well with the biggest successfull percentage at 81.96%.. Key wordsAlat Bantu, auto fokus, Contrast Measure, co-occurrence matrix, Sel Darah, Sel Darah Putih, Sel Darah Merah.